Choral Editing of M.Leontovych as a Means of Creative Activity of Pupils in Formation of the Future Specialist (Course „Choral Arrangement”) - Zaverukha, Stepan (Pedagogical Discourse, 2012)
Certain processes of formation of creative activity of students by means of choral editing of M.Leontovych during the course „Choral Arrangement” have been revealed in the article. Ways and methods of stimulating music-creative activity directed to the future specialist formation have been studied